Introgression of staygreen QLT's for concomitant improvement of food and fodder traits in Sorghum bicolor - Blümmel, Michael; Deshpande, S.; Kholová, Jana; Vadez, Vincent (Elsevier, 2015)
Staygreen quantitative trait loci (QTL) were introgressed into sorghum genetic backgrounds S-35 and R-16 generating 52 and 39 lines, respectively, to investigate the effects of staygreen introgression on stover fodder traits and grain–stover relationships. Trials were conducted in the post-rainy seasons 2008–2009 and 2009–2010 at ICRISAT headquarters using a fully irrigated control and a terminal water stress treatment. Stover fodder quality traits analyzed were nitrogen (N), in vitro organic matter digestibility (IVOMD), acid detergent fiber (ADF), acid detergent lignin (ADL) and neutral detergent solubles (NDS = 100 − NDF) using a combination of conventional nutritional laboratory analysis with Near Infrared Spectroscopy (NIRS). Significant (P < 0.0001) differences were found among lines for grain and stover yield and all stover fodder quality traits under both water treatments. Water treatment had greater effects on grain and stover yields, which decreased between 20 and 32% under water stress, than on stover fodder quality traits which varied at most by 8% between treatments. Year had the greatest effect (F-value) on all traits followed by water treatment and line. Trade-offs between stover quality traits and grain yields were largely absent in both backgrounds. Year and water treatment had larger effects on stover fodder quality traits than QTL's but QTL's were highly significant (P < 0.0001) except for stover N in S-35 background. Significant interactions between QTL, water treatment and year were largely absent. The effect of QTL on selected stover fodder quality traits was background dependent. In S-35 one staygreen QTL (StgB) increased stover IVOMD and grain and stover yield while no concomitant trait improvement was observed in background R-16. It is concluded that staygreen QTL can contribute to improving stover quality and grain and stover yield in a background-dependent manner.